What do We Know about Consumers’ Price Perception? Research Findings of Studies in Sociology and Marketing Science - Berdysheva, Elena (Journal of Economic Sociology, 2014)
The article argues that economic sociologists underestimate the problem of consumers’ price perception in their studies while it may be used as an effective key to the social orders of modern markets. Sociological studies of consumers’ price perception are very few and mostly performed at the theoretical level so the author makes an attempt to draw colleagues’ attention to the results of price perception research undertaken within marketing science and overviews its results in the light of sociological tasks. It is assumed that the problem of price perception is a ground for fruitful cooperation between these two disciplines. At the same time, the main message of the work has nothing to do with the discourse on interdisciplinarity. It is focused on the social base of consumers’ price perception and price behavior. The primary objective of the article is to shed light on the social contexts relevant for perception and interpretation of market prices by social actors. Overviewed literature enables to state that the perception of price and pricing behavior (defined as the set of possible decisions about price which depends on the way a consumer perceives and interprets it) is modulated by the social position of the individual. The main distinction lies between economizing practices driven by the budget constraints and consumers’ cognitive ability and aspiration to manage price behavior rationally. It is shown that internal standards used by consumers for estimation current prices are shaped within social interaction beyond the market, especially through the everyday storytelling. The relationship between social value and market prices of goods are in the center of the paper. The author claims the inseparability of the monetary value from the socially constructed image of the goods and underlines the price-quality dilemma as an urgent issue for the contemporary economy with its non-stop process of qualification and requalification of market commodities. Talk about price perception can not pass by the problem of social meanings of different price levels and, especially, by the social nature of discounted prices. The last goes hand in hand with market price fairness as it is seen by consumers. Thus, the section devoted to this problem logically follows. Conclusive part of the paper is devoted to the possible research questions for the future studies of consumers’ price perception, which appear when we build bridges between marketing and sociological research.